Kompetensi Guru dalam Menerapkan Model Pembelajaran Two Stay Two Stay untuk Meningkatkan Prestasi Belajar Siswa - Krismoni Krismoni; Nuzuar Nuzuar; Baryanto Baryanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this research is to know the competence of teachers in implementing the learning model of Two Stay Two Stay (TSTS) to improve the learning achievement of grade VII students of SMP 27 Rejang Lebong Desa Durian Mas. This research is qualitative research, with observation, interview and documentation data collection techniques. The data analysis techniques used are data collection, data selection, display data and conclusion retrieval. The results of the study, obtained 3 things related to the learning benefits of the two stay two stay model, first, the competence of teachers in applying learning models to improve the learning achievement of students is already good, and teachers convey the material as usual, forming groups and students more eager to learn and more active. With the learning model Two Stay Two Stay makes students feel themselves getting attention and the opportunity to express opinions, ideas and ideas. Both Two Stay Two Stay Lessons have advantages in improving students' learning. All three student learning outcomes after the teacher applied the learning model to PAI subjects have already shown success. This can be seen from the results of replays and assignments, either in groups or individually. In conclusion, the learning model of Two Stay Two Stay has been well run by pai subject teachers and provides positive results in improving the learning outcomes of grade VII students of SMP 27 Rejang Lebong Desa Durian Mas. Keywords: Learning, Teacher competency, Two Stay Two Stay, learning achievement